Body fat percentage and the outcomes of hip fractures in adults aged 50 years and above: a 1-year follow-up study - Fan, Wenliang; Zhao, Zhibang; Wang, Liqiang; Chu, Qingbo (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the relationship between body fat percentage (BFP) and postoperative outcomes, including mortality and free ambulation rates, in older adults following hip fracture surgery over a 1-year follow-up period.MethodsAn observational cohort study was conducted at a single trauma center in China from January 2014 to January 2022, enrolling 895 patients (299 males, 596 females) aged ≥50 years with surgically treated hip fractures. BFP was measured via bioimpedance analysis (BIA) at admission. Cox proportional hazards and logistic regression models were employed to assess associations between BFP and outcomes, adjusting for confounders. Restricted cubic splines identified optimal BFP thresholds.ResultsA non-linear relationship between BFP and mortality was observed in both sexes. Optimal BFP ranges were 19.49–27.28% for males and 25.39–32.64% for females. Deviations from these ranges significantly increased mortality risk (adjusted HR for high vs. middle BFP: males 2.27, 95% CI 1.16–4.43; females 2.00, 95% CI 1.15–3.46) and reduced free ambulation rates (p < 0.05). Sex-specific differences emerged: high BFP independently predicted poorer outcomes in males, while both low and high BFP were detrimental in females.ConclusionExtremes in BFP—either low or high—are associated with elevated mortality and impaired functional recovery after hip fracture surgery, underscoring the dual role of adiposity in postoperative prognosis.